Taxing Agriculture in Pakistan - Khan, Mahmood (IMF Policy Discussion Papers; Policy Discussion Paper ;, 1998)
Pakistan's economic performance has been marred by persistently high fiscal deficits which have resulted largely from the inability to raise sufficient revenues. Agriculture is a dominant sector of the economy, but generates very limited revenue from direct taxes on agricultural producers. The paper first reviews the history of attempts to tax agriculture in Pakistan, the purpose of which is to underscore the difficulty in adopting and implementing a sound agricultural tax policy. It then examines various alternatives with regard to the taxation of agricultural land and incomes. Finally, it presents the outlines of a full-fledged agricultural income tax that could be implemented within the Constitutional framework in the next three to five years.